APPLICATION OF DISCUSSION METHOD IN IMPROVING STUDENT LEARNING OUTCOMES IN PAI SUBJECTS - Faisal Faliyandra; Abdelmajid Idris Mohammed Khalil; Makhrus Ali, M. (International Journal of Multidisciplinary Reseach, 2025)
Achievement​ results Study past order method discussion Can tried with evaluation. Evaluation is a series activity use take into account something activity so that recognize throughout the activity the Already bear fruit results. The formulation of the problem in this study is "What is the order method discussion can increase results Study student on eye "Islamic Religious Education lessons at SMP Setia Probolinggo?" There is also a goal of this research, namely to identify how the implementation of discussion procedures can improve student learning outcomes in Islamic Religious Education subjects at SMP Setia Probolinggo. The research method used is classroom action research (CAR). This research is included in the type of meta-analysis research, namely research conducted by summarizing, reviewing and analyzing research data from several previous research results. The results of the study indicate that an increase in student grades in Islamic Religious Education learning using the discussion method in class VIII students of SMP Setia Probolinggo can be seen from the results of student scores in each cycle where in the first cycle the increase in learning completeness was 7 students or 30.4% increasing to 21 students or 91.2% experiencing an increase, while in the second cycle there was another increase of 23 students or 100%. This means that the application of the discussion method that has been used in Islamic Religious Education learning is declared successful in improving student learning outcomes.